Chapter Il testo bergamasco: archivio e mappatura delle relazioni culturali tra la città di Bergamo e la Russia - VISINONI, Alessandra Elisa (Biblioteca di Studi Slavistici, 2019)
This article presents the "Russo-Bergamo Map Collection" (Cartoteca russo-bergamasca, ), a website representing the culmination of a research project conducted at the University of Bergamo under the title "Archiving and Mapping Cultural Relations between Bergamo and Russia". Comprised of thirteen thematic sections, the site illustrates our reconstruction of cultural ties between Bergamo and Russia over the course of the last four centuries.